A leitura sob a ótica midiática : uma breve reflexão pela análise de discurso - Almeida, Carla Correia de (2019)
Reading and writing are matters of social interest. Many studies and debates involve this theme because of problems with teaching-learning. In this perspective, the subject is often crossed by discourses based on the ideology of school failure due to the supposed difficulty in developing abilities to read and understand texts. This discourse of failure with the reader's abilities circulates in society, in the academic circles, in the media, finally it is a discursivity that is based on techniques or school skills, or even in the cognition, but that does not consider the historicity and constitutive discursive and ideological formations of the subject as a reader and that cross the question. This work intends to address the effects of meaning produced by discursive materialities that deal with the theme "Reading" in some copies of Veja Magazine and the Portuguese Language Knowledge Magazine, between the years 2000 and 2017, making a counterpoint between these discursivities and analyzing the construction of the reader-subject they bring. It was tried to develop an analytical work, reflecting on the concept of subject, thought by Michel Pêcheux, after the readings of the works of Althusser and Lacan, and worked by Eni Orlandi, theoretical bases of this study. The objective is to understand how the subject-reader form is produced in the discourse of these media, besides analyzing the ideological formations that form such materialities. Thus, as a theoretical-analytical device, we can observe the discursive and ideological formations that constitute them, as well as the relations of paraphrase and polysemy that they put into operation. The central question is to analyze the corpus through the cutouts, noting the discursive and ideological formations that are produced in the discursive thread of the media quoted on the subject form and how the subject-reader form is constructed. The methodological procedures were based on a bibliographical review, making possible the reflection on the concept of subject that belongs to AD and taking into account the analysis of the corpus. Thus, the reflection on the ideological formations that constitute the subject - reader form in these journals - a popular one, another one directed to those interested in the area - can guide the main points in the relationship with the problems found in reading comprehension. In the corpus analyzed, the three materialities are crossed by traditional ideological formations of education that, while trying to seek innovative paths with new theories, has the discourse always ruled as having a culprit, in this case, either the student or the teacher, or the school. The discursive reading event is always based on school failure. There is no reflection based on exteriority, in which the conditions of production that were part of the beginning of the school institution and, hence, of teaching-learning are considered, not being for everyone with the same conditions. The system of production and reproduction of social classes has also been brought to education and influencing this event. And the previous discourses are reproducing in a paraphrastic relationship in which the same ideology is always reformulated. Therefore, this observation is relevant by the discursive bias, so that one can understand these prevailing discourses, because it is the discourse of the ruling class. Thus, observing this socio-historical relationship, it is possible to rethink such discourses and understand reading gestures in another way, transforming practices in school and in society.